The garden of evening mists - Tan, Twan Eng, 1972- (Myrmidon, 2012)
It's Malaya, 1949. After studying law at Cambrige and time spent helping to prosecute Japanese war criminals, Yun Ling Teoh, seeks solace among the jungle fringed plantations of Northern Malaya where she grew up as a child. There she discovers Yugiri, the only Japanese garden in Malaya, and its owner and creator, the enigmatic Aritomo.